Vilniaus krašto folkloras kaip tautinės tapatybės dėmuo - Matulevičienė, Saulė (Literatūra, 2015)
The article focuses on the movement at the end of the 19th and the beginning of the 20th centuries that manifested itself in the collecting, researching and publishing of Vilnius Region folklore. Saulė Matulevičienė speculates as to what degree this activity can be associated with conscious efforts to define and consolidate the limits of the historical and cultural indentity of the population of this Region. She also questions what, if any, ideological motivations this activity might have had.The discussion of the current affairs of the Vilnius Region is done in the background of more generalised reflections such as what role is attributed to the folklore when the symbols of the identity of a certain community are consciously brought forward or even created anew; which folklore text and how they gain symbolical significance and thus help to bring a community together. At the end of 19th century, linguistically diverse folklore texts of the Vilnius Region were written down and published and neither the ethnic background of their presenters nor the language of the actual texts were considered as important and distinguishing aspects of identity of the population of the Region.As of the establishment of the Lithuanian Society of Science at the beginning of the 20th century, the Lithuanian character of the Region was being promoted as a reaction to a rapid decline and intense extermination of the ethnic Lithuanian population. Thus, collecting and researching of the folklore develops a defensive character. Manuscript collections of the time reflect a diverse living tradition covering different stylistic modes attributed to different points in time. The selection of texts published in the folklore collections of the time becomes not only the symbolic consolidation of the Lithuanian identity of the inhabitants of the Vilnius Region, but also contributes to the construction of this identity.The political and historical circumstances of the 20th century did not favour the documentation of the old multilingual traditions present at the border regions. They were documented a lot later and have so far been little researched.